2017
DOI: 10.1371/journal.pone.0174708
|View full text |Cite
|
Sign up to set email alerts
|

Creating an automated trigger for sepsis clinical decision support at emergency department triage using machine learning

Abstract: ObjectiveTo demonstrate the incremental benefit of using free text data in addition to vital sign and demographic data to identify patients with suspected infection in the emergency department.MethodsThis was a retrospective, observational cohort study performed at a tertiary academic teaching hospital. All consecutive ED patient visits between 12/17/08 and 2/17/13 were included. No patients were excluded. The primary outcome measure was infection diagnosed in the emergency department defined as a patient havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
213
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 243 publications
(220 citation statements)
references
References 21 publications
5
213
0
2
Order By: Relevance
“…The World Health Organization estimates that more than six million people die of sepsis annually, and many of these deaths are preventable [2]. In the United States, severe sepsis Previous studies have shown that machine learning (ML) models trained from data in individual patient electronic health records (EHR) may be used for the early detection of sepsis [7,8,9,10,11,12]. The ML models for sepsis detection far exceed the predictive ability of existing clinical early warning system scores, such as the National Early Warning Score (NEWS) [7,9,10,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization estimates that more than six million people die of sepsis annually, and many of these deaths are preventable [2]. In the United States, severe sepsis Previous studies have shown that machine learning (ML) models trained from data in individual patient electronic health records (EHR) may be used for the early detection of sepsis [7,8,9,10,11,12]. The ML models for sepsis detection far exceed the predictive ability of existing clinical early warning system scores, such as the National Early Warning Score (NEWS) [7,9,10,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning techniques excel in the analysis of complex signals in data-rich environments 11,12 . Recent advances in deep learning, reinforcement learning, and other machine learning techniques have enabled and popularized their use in mathematics 13 , engineering 14 , biology 15 and medicine [16][17][18][19][20][21][22][23][24][25][26]77 . The abundance of data collected in the ICU and the importance of timely decision-making are key to the growing interest of using of machine learning in this setting.…”
mentioning
confidence: 99%
“…It is important to note that we designed the study as a classification task rather than a time-to-event modeling experiment, because the former is significantly more common in the literature [28][29][30][31]. The alternative would not allow for the use of an established, standard set of performance metrics such as AUROC and specificity without custom modification, and would make it more difficult to compare the present study to prior work in the field.…”
Section: Limitationsmentioning
confidence: 99%